PENGARUH MOTIVASI BELAJAR TERHADAP HASIL BELAJAR SISWA DALAM PEMBELAJARAN DARING - Nurfaliza, Nurfaliza; Hindrasti, Nur Eka Kusuma (Jurusan Ilmu Pendidikan Fakultas Keguruan dan Ilmu Pendidikan Universitas Riau, 2021)
Online learning leaves behind as problems that make students' learning spirit decrease. Giving encouragement and motive to students is expected to be able to adjust even though the situation is difficult to compromise. This is what happened to one of the students of SMP Negeri 3 Bintan Timur who felt that during online learning his learning achievements improved and learning motivation was a factor that influenced the success gained. This study is a case study with qualitative approach that seeks to explore the motives of the subject in improving learning outcomes, especially in online learning. Researchers collected data using interview techniques directly to subjects and parents as well as questionnaires through google forms to teachers and friends of the subject, with a total of two people each. Furthermore, data processing is done by analyzing students' problems, then seeking information from sources or people closest to the subject and finally finding the motives of the subject in improving learning achievement. The results showed that the provision of learning motivation can improve the learning outcomes of the subject, this is proven by the subject successfully becoming an outstanding student in the classroom. The purpose of this research is to explore the motivation of learning the subject and know the role of parents, teachers and friends in providing learning motivation. With this research can contribute to students, teachers and parents that the motivation of learning is very necessary to grow in order to strengthen the desired goals can be achieved.